Challenges for the International Tourism Industry in Japan – An Agent for Economic Recovery and Development - Zhang, Rong; McCornac, Dennis C. (Almatourism - Journal of Tourism, Culture and Territorial Development, 2014)
Japan’s successful bid to host the 2020 Summer Olympic Games in Tokyo is expected to bring a windfall to the tourism industry with an increasing number of visitors coming from abroad. Taking advantage of this opportunity to develop the newly-emerging tourism industry will be major task, but one that can significantly impact the future development of the country. The purpose of this paper is to undertake a review of the current situation of international tourism in Japan and examine the problems which may limit the international competitiveness of Japan’s tourism industry. We offer a number of solutions on how to improve tourism quality to better address the expectations of foreign visitors and for Japan to meet the goals of the Tourism Nation Promotion Basic Law (Act No.117 of 2006) which defines the basic plan for “Realizing a Tourism Nation”.